Hiring Standards and Market Clearing - Ekkehart Schlicht (Institute for the Study of Labor (IZA), 2002)
Consider a labour market with heterogeneous workers. Firms recruit workers by fixing a hiring standard and a wage offer simultaneously. A more demanding hiring standard necessitates a better wage offer in order to attract enough qualified applicants. As a result, an efficiency wage effect is obtained. An equilibrium emerges which does not clear the labour market. The wage level depends on structural characteristics of labour supply, such as heterogeneity and mobility of the workers. The model is contrasted with prevailing efficiency wage theories, and policy implications are also discussed.
Keywords: J41; J31; 330; wage formation; hiring standards; efficiency wages; unemployment; Arbeitsmarkttheorie; Effizienzlohn; Arbeitsnachfrage; Qualifikation; Lohn; Theorie der Arbeitslosigkeit; Theorie